Adaptive Variability of Cognitive Modelling of Lexical Semantics - O. V. Valko (Научный диалог, 2018)
The article is devoted to the issues of cognitive modelling of the semantics of English nouns denoting a criminal. The article deals with the question of the variable representation of cognitive information due to adaptive potential of knowledge representation structures depending on the language level and the essence of the phenomenon under study. The results of the analysis of lexical units and their actualization in the literary text are presented. Particular attention is paid to the structures of knowledge representation like frame, prototype, cogniotype and stereotype. The novelty of the research is seen in the fact that the work implements a cognitive approach to the study of the semantics of units and the content and structural aspects of the text. Within the framework of this approach, cognitive structures of different levels are involved. The conclusion is made about the complementarity of these structures and about the possibility of their simultaneous functioning. In addition, the paper attempts to formulate rules and principles of cognitive text research. The relevance of the research is caused by the attempt to identify the laws of categorization and conceptualization of reality reflected in the language. The results of cognitive research, usually presented in the form of models or schemes, facilitate subsequent comparison of ways of categorization in other languages, as well as the identification of common universal laws of human cognition and the principles of its reflection in semantics.